Saltiness enhancement of oil roasted peanuts induced by foam-mat salt and soy sauce odour - Chokumnoyporn N. (2017)
Â© 2016 Institute of Food Science and Technology. Odour-induced saltiness enhancement (OISE) method can be used to reduce salt in food. This study was performed to examine the effect of OISE on saltiness perception of oil roasted peanuts seasoned with foam-mat salt. First, 410 consumers rated saltiness intensity elicited by odour names of fifty-seven food/ingredient items. Soy sauce odour name was among from the top five items with higher saltiness intensities, hence it was selected to further investigate the effect of saltiness enhancement in conjunction with foam-mat salt. The control (commercial salt, 100%), CS50 (commercial salt:soy sauce odour; 50:50) or FS50 (foam-mat salt:soy sauce odour; 50:50) was mixed with roasted peanuts, which were subsequently evaluated by a descriptive panel for saltiness intensity and by consumers for sensory acceptance. OISE in conjunction with foam-mat salt produced FS50 roasted peanuts, having 10 mg of sodium per 100 g sample less than CS50 but being as acceptable as the control.